Collective Action, Good Government, and Democracy in Tlaxcallan, Mexico: An Analysis Based on Demokratia - Fargher, Lane F.; Blanton, Richard E.; Heredia Espinoza, Verenice Y. (Frontiers in Political Science, 2022)
For nearly 200 years, Western social science has argued that good government, embodied in democracy, originated exclusively in Western Europe and was introduced to the rest of the world. This Eurocentric vision has profoundly shaped social science's approach to the non-Western World (and pre-modern Europe). Importantly, distinct theories (e.g., Oriental Despotism, Substantivism, etc.) were developed to address premodern state-building in Asia, the Near East, Africa, and the Americas because “normal approaches” could not be applied in these areas. Regardless of the approach and the geographical area, Europe inevitably appears at the pinnacle of social evolutionary change. However, recently, Eurocentric theories have been subject to reevaluation. In this paper, we pursue that critical agenda through a comparative study of demokratia's original formulation and ask: would a 5th century B.C.E. Athenian recognize democratic attributes in 15th century C.E. Tlaxcallan, Mexico? We answer this question by first summarizing literature on Classical Athens, which concludes that among the key values of demokratia were isonomia and isegoria and then explore the evidence for similar values in Tlaxcallan. Our response is that an Athenian would see strong parallels between his government and that of Tlaxcallan.